Empowering Youth of Productive Age in the Midst of the COVID-19 Pandemic Through Entrepreneurial Skills in Limau Mungkur Village, Binjai City - Siregar, Onan M; Marpaung, Nicholas (Talenta Publisher, 2023)
The problem faced is the number of productive age youth who cannot increase their income because the Covid-19 pandemic makes limited mobility of the community. In addition, a lot of time spent at home without doing productive activities so that entrepreneurship activities through online media become one of the solutions to increase income. The purpose of this community service is to provide business skills to young people of productive age during the Covid-19 Pandemic through online media. This community service is addressed to young people of productive age in Limau Mungkur Village of Binjai City. The method used in achieving these goals is by socializing and lecturing about business management through Facebook and Instagram and practicing making dimsum and tumpeng mini. This skill training is used to make online sales to social media users and is used to create a strategy to sell dimsum and nasi tumpeng mini to be purchased by the community. Through empowerment carried out, young people of productive age become very enthusiastic to do entrepreneurial activities by utilizing social media such as Facebook and Instagram.